THE ROLE OF ACTIVITIES IN A PERSONALITY-ORIENTED ENGLISH LESSONS - Shirova, Madina Sunnatillo qizi; Ziyodullayeva , Aziza Akmalovna (GOLDEN BRAIN, 2024)
The article explores the specific features of the teacher's and students' activities in an English language lesson with a personality-oriented focus, as well as the main aspects of their own research aimed at improving the learning process and effectiveness of educational standarts.